Differential impact of the Bisphosphonate Alendronate on undifferentiated and terminally differentiated human myogenic cells. (6th November 2013) - Shiomi, Kosuke; Nagata, Yuki; Kiyono, Tohru; Harada, Atsushi; Hashimoto, Naohiro
Abstract: Objectives: Alendronate, a nitrogen-containing bisphosphonate, is well established as a treatment for osteoporosis through regulation of osteoclast activity. Previously, the pharmacological effects of bisphosphonates on cells outside the bone environment have been considered irrelevant because of the bone-targeting property of bisphosphonates. However, the chronic effects of bisphosphonates on tissue-neighbouring bone, in particular skeletal muscles, should not be ignored because patients are treated with bisphosphonates for long periods. Methods: Here, we show that the impact of alendronate on immortalized human myogenic cells depends on growth and differentiation-inducing conditions. Key findings: Alendronate disrupted cytoskeletal structures and prevented migration, proliferation and differentiation of undifferentiated human myogenic cells that are involved in muscle regeneration. In contrast, alendronate did not affect the morphology, gene expression or survival of terminally differentiated human myotubes. Conclusions: The present results suggest that the muscle regeneration capacity of osteoporosis patients treated with bisphosphonates for long periods may be attenuated. The present research on the pharmacological effects of alendronate on cultured human myogenic cells will contribute to improvement of therapeutic strategies and optimization of rehabilitation programmes for locomotive activity in osteoporosis patients treated with bisphosphonates.